Acoustic insulation and absorption mechanism of metallic hollow spheres composites with different polymer matrix. (15th September 2020) - Yu, Tianmiao; Jiang, Fengchun; Wang, Jiahao; Wang, Zhenqiang; Chang, Yunpeng; Guo, Chunhuan
Abstract: In this study, the polyurethane/316L stainless steel hollow spheres (PU/316L HS) and silicone rubber/316L stainless steel hollow spheres (SR/316L HS) composites were prepared by casting method. The sound transmission loss of polyurethane composites and silicone rubber composites increased after adding metallic hollow spheres. The sound insulation performance of hollow sphere composite is closely related to the acoustic reflection and diffraction at the interface. In addition, silicone rubber with better molecular flexibility is easier to reflect sound waves than polyurethane, thus reducing the passing sound energy, so it has greater sound transmission loss. For the sound absorption performance of materials, the PU has a maximum absorption coefficient of 0.87 at 3550 Hz, but the absorption coefficient of the PU/316L HS composite moved to the lower frequency. The reason for this phenomenon is that the hollow spheres change the elastic modulus of polyurethane, which causes the resonance frequency of material and air to move to lower frequency, so the range of sound absorption frequency changes. Moreover, the different proportion of free volume in polyurethane and silicone rubber matrix is the main reason for the great difference of their sound absorption properties.